Migraine and Tension-Type Headache - Kahriman, Azmin; Zhu, Shuhan (Seminars in Neurology, 2018)
Migraine and tension-type headache (TTH) are common primary disorders that carry significant morbidity and socioeconomic effect. In this article, we will review the epidemiology, presentation, and diagnosis of these disorders. First-line acute treatment for migraine consists of analgesics, triptans, and antiemetics, while nonsteroidal anti-inflammatory drugs are the mainstay treatment for TTH. Patients with frequent or chronic headaches warrant prophylactic therapy. For migraine, various classes of preventives can be used (β-blockers, tricyclics, antiepileptics, botulinum toxin), with the choice of therapy tailored to the patient's risk factors and symptoms. For TTH, tricyclics have the most evidence as prophylactic therapy. A new class of medication, monoclonal antibodies to calcitonin gene receptor peptide or its receptor, became available in 2018, and is the first class of medication specifically designed to treat migraine. In addition to pharmacotherapy, we will also review nonpharmacologic interventions as well as neuromodulation for migraine.
Keywords: migraine; tension-type headache; chronic migraine; acute treatment; preventive treatment